From Husserl to Moscovici: Phenomenological Thinking in the Theory of Social Representations (Revista de Psicología, 2024)
Emerging in France in the 1960s, Social Representations Theory has experienced significant growth, marked by empirical and methodological contributions. However, the exploration of its philosophical foundations remains largely overlooked. This article seeks to address this gap by adopting a phenomenological approach to understanding social representations as forms of common sense knowledge. Drawing upon Husserl's concepts of the natural attitude and life world, this study theorizes a subject that is receptive, active, and interpretive, shaping meaning within the context of social interactions and culture. Through the lens of social representations, individuals render reality familiar and engage in dialogues that give rise to multiple perspectives, thus shaping the structure of the world. By integrating phenomenological insights, this article aims to enrich our understanding of social representations and their role in shaping our collective understanding of reality.
Keywords: Social representations; natural attitude; life world